NEW WIRELESS NETWORK PROTOCOLS: ADVANTAGES AND DISADVANTAGES - LEVCHENKO, SERGIY; PEREVERZEV, ANTON; PODVIZHENKO, ARTEM; NIKOLAIEVSKYI, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The authors examines the issues of Wireless Networks, which are the foundation of modern communication, providing Internet connectivity for millions of devices worldwide. With the advancement of technology, new protocols are emerging that promise improvements in speed, reliability, and security. This article will review the latest wireless network protocols, such as Wi-Fi 6 (802.11ax), Wi-Fi 6E, Wi-Fi 7 (802.11be), and 5G, as well as their advantages and disadvantages. The growing number of connected devices requires networking solutions that can easily scale without sacrificing performance. In a world where there are many different devices and systems, the latest protocols must ensure interoperability between different manufacturers and technologies. Therefore, the problems of the latest wireless network protocols are closely related to important scientific and practical tasks facing modern society. Studying the advantages and disadvantages of these protocols is critical to ensure the efficient functioning of wireless communications in the future. The influence of the implementation of the latest protocols on the practical use of wireless networks in various fields, including communications, medicine, and industry, will be evaluated. An analysis of the competitiveness of the latest protocols in comparison with previous versions of the protocols and other competing technologies was also carried out, and recommendations were formulated for organizations and enterprises regarding the selection and implementation of the latest wireless network protocols, taking into account their advantages and disadvantages. Given an example with Wi-Fi 6, I used the Scapy library to create and send frames. This example demonstrates how you can configure frames for data transmission using Wi-Fi 6 technology. Using RadioTap and Dot11 allows you to configure the necessary parameters for wireless transmission.